Meningkatkan Kepuasan Pelanggan dengan Peran Komunikasi Interpersonal yang Tepat dan Waktu Tunggu - Hielvita Ludiya Ludiya (LPPM and Travel Operation Department Universitas Asa Indonesia, 2021)
Companies expect businesses to grow and develop. For this satisfaction has been an important issue in any business, by designing a good service is expected to satisfy consumers. This study aims to examine the impact of employee friendliness, respectfulness, helpfulness, waiting time on customer satisfaction with focus on low cost airlines. A total of 100 completed responses were collected in the survey. The sampling method in this research is simple random sampling. The data analysis used SmartPLS 3.0 as software. The findings of this research showed that employee friendliness, helpfulness, waiting time have positive and significant impact on customer satisfaction. Respecfulness have negative and unsignificant impact on customer satisfaction. This study have several limitations such as taking only two airliness of low cost carrier airliness which become the object of research. The managerial implications of this study provides suggestions for airlines service enterprises to further improve their service impact of respectfulness. Further investigation needs to be expanded by taking some of the objects that are similar research at the airlines too or other industry and by increasing the sample size to improve the results of consistency.